WUSCHEL controls meristem function by direct regulation of cytokinin-inducible response regulators: letters - Leibfried, Andrea; To, Jennifer P. C.; Busch, Wolfgang; Stehling, Sandra; Kehle, Andreas; Demar, Monika; Kieber, Joseph J.; Lohmann, Jan U. (Nature, 2005)
Plants continuously maintain pools of totipotent stem cells in their apical meristems from which elaborate root and shoot systems are produced. In Arabidopsis thaliana, stem cell fate in the shoot apical meristem is controlled by a regulatory network that includes the CLAVATA (CLV) ligand-receptor system and the homeodomain protein WUSCHEL (WUS). Phytohormones such as auxin and cytokinin are also important for meristem regulation. Here we show a mechanistic link between the CLV/WUS network and hormonal control. WUS, a positive regulator of stem cells, directly represses the transcription of several two-component ARABIDOPSIS RESPONSE REGULATOR genes (ARR5, ARR6, ARR7 and ARR15), which act in the negative-feedback loop of cytokinin signalling. These data indicate that ARR genes might negatively influence meristem size and that their repression by WUS might be necessary for proper meristem function. Consistent with this hypothesis is our observation that a mutant ARR7 allele, which mimics the active, phosphorylated form, causes the formation of aberrant shoot apical meristems. Conversely, a loss-of-function mutation in a maize ARR homologue was recently shown to cause enlarged meristems.